In vitro production of early stage buffalo embryos in modified synthetic oviductal fluid (mSOF) medium - SHARMA, A K; PURI, GOPAL; KHARADI, V B; BHAVSAR, S K (The Indian Journal of Animal Sciences, 2018)
The objective of the present study was to observe the developmental rates and the stage of development since fertilization of in vitro produced early stage buffalo embryos. Buffalo cumulus-oocyte complexes (COC’s) obtained from slaughterhouse ovaries were matured and fertilized in vitro. The fertilized oocytes (400) were then cultured in modified synthetic oviductal fluid (mSOF) medium containing bovine serum albumin (BSA) and fetal bovine serum (FBS) and evaluated for the developmental stages of preimplantation early stage embryos up to morula on 48 h, 72 h, 96 h and 7th day post fertilization. Highest percentage of 8 cell embryos were obtained followed by 16 cell, 2 cell, 4 cell and morula at the end of in vitro culture (IVC). Similarly, the mean embryo percent of 2 cell, 4 cell, 8 cell, 16 cell and morula stage at the end of IVC was 8.20±1.28, 6.50±0.97, 12.19±1.03, 11.83±0.96 and 5.27±0.87. The overall embryos developed at the end of IVC were 43.98±2.11%. The percentage of oocytes which arrested and subsequently degenerated were 56.02% till day 7 post-insemination. It can be concluded that early stage buffalo embryos till morulae can be produced by using modified synthetic oviductal fluid (mSOF) medium as embryo development medium but for further development, the supplementation of different growth factors required.